Implementasi Ekstrakulikuler Seni Baca Al-Qu’ran dalam Menggali Potensi Peserta Didik MI Masjid Al-Akbar Surabaya - Faizah, Esa Nur; Ummah, Khoirotul; Islamiyah, Madinatul; Rahmawati, Sonia (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
One way to realize a golden future of achievement in the millennial era is to explore the potential of the nation's generation, which can be done from an early age, especially at the elementary school level. The purpose of this study was to find out how the implementation of the extracurricular art of reading the Qur'an at MI MAS and to find out the obstacles in the implementation of the extracurricular art of reading the Qur'an.This research method uses a qualitative descriptive approach. Data collection techniques through Observation, Interviews, and Documentation. The data sources used are primary and secondary data sources. Data analysis in the field uses data reduction, data display, and conclusion drawing (verification). Data validity techniques use source triangulation.The implementation of the extracurricular art of reading the Qur'an at MI MAS was carried out in 3 stages, namely preparation, implementation and evaluation. In the preparation aspect, educators prepare and plan activities that will be carried out by students. In the implementation process, educators begin activities by writing down the formula of the song that will be learned by students and writing it on the board. In the evaluation stage, practicing the songs that have been taught using different verses of the Qur'an from those taught by educators. The obstacle in implementing the extracurricular art of reading the Qur'an is that lower-class students are still very difficult to condition, making the process of learning the art of reading the Qur'an less than optimal.